The Constitutionality Of The Practice Of Euthanasia Against Parents In Maqashid Sharia And Human Rights - Candra, Anton Afrizal; Haji Abdullah, Raihanah Binti (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
Efforts to take a conscious action that can hasten the death of a person due to compassion and pity for the condition experienced by that person is called euthanasia or